Do we prioritize floodplains for development and farming? Mapping global dependence and exposure to inundation. (November 2021) - Dryden, Rachel; Anand, Mira; Lehner, Bernhard; Fluet-Chouinard, Etienne
Highlights: Human population density in inland floodplains is 3x more than the global average. One third of urban areas may experience regular, seasonal, or infrequent flooding. A quarter of the world's cropland may depend on or be exposed to flooding. Nearly one fifth of global roads are located in flood-prone regions. Dependence and exposure to flooding varies regionally, with its peak in South Asia. Abstract: Global wetlands and floodplains offer benefits and perils alike for human society. For example, humans rely on natural flood cycles for fisheries and agriculture, yet flooding also caused nearly one trillion USD in damage in the past 30 years and impacts millions of people every year. Looking forward, altered flow regimes or increased drought conditions are expected to affect the natural inundation cycle and its ecosystem services. The current and potential future impacts of flooding and drying events warrant increasing efforts to quantify our dependence and exposure within flooded areas, since any change from current inundation patterns is expected to have consequences for those who rely on regular flood occurrences. This paper provides a baseline global assessment of the dependence and exposure of human populations, urban areas, roads, and agriculture on current inundation patterns. The analysis uses a spatially explicit inundation map at ∼500 m resolution (GIEMS-D15) derived from satellite remote sensing to represent flooding extents and overlays it with current population and land use maps. We find that 35% of the analyzed population, or 2.0 billion people, live inside areas that are prone to inland flooding, which comprise only 12% of the land surface area (excluding marine coastal areas), confirming that population densities within inundation zones are about three-times above global average. Likewise, 35% of urban areas potentially experience regular, seasonal, or infrequent flooding. Agriculture shows a similar pattern with 24% of the world's cropland in areas of recurring inundation. Finally, we estimate that 18% of the global road network is exposed to inundation during high water periods. These global estimates demonstrate a preferential tendency of human populations, infrastructure, and agriculture to be co-located within inundation areas, making related anthropogenic activities highly susceptible to future changes in flood regimes. The results are intended to offer a suite of first-order estimates as partial input to more holistic risk and vulnerability assessments and to ultimately improve environmental planning and policy at large scales.